(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article we provide information about using phrases which contain sewing terms in literature in order to portray people’s characters and attitudes to situations. We analysis some authors and their works, their ability to use phrases which includes sewing terms metaphorically. We also give extracts from the books to show vivid examples and help readers to define the real meaning